EFFECTIVENESS OF PEEIM AND INTERACTIVITY AS A STRATEGY FOR INCREASING PURCHASING INTENTION IN FACING GLOBAL MARKET COMPETITION IN INDONESIA DURING THE 4.0 MARKETING ERA: A SURVEY ON TOP THREE FOREIGN MARKETPLACE CUSTOMERS IN THE INDONESIAN ONLINE MARKET - Suryono I.A. (Russian Journal of Agricultural and Socio-Economic Sciences, 2020)
Marketplace competition in Indonesia is getting tighter, both Indonesian and foreign marketplaces. This research objectives is to measure the influence of customer satisfaction on repurchase intention through customer trust using PEEIM as the moderation, measure the effect of effective use of instant messengers and effective use of feedback systems on interactivity, measure the effect of interactivity on customer trust, and measure the effect of interactivity on repurchase intentions which is moderated by PEEIM in which the data is taken from customers of the top three foreign marketplaces in the Indonesian online market, so that a strategic concept of online business will be obtained in building the trust of the Indonesian people using PEEIM and Interactivity. Respondents in this research are most of the customers of the top three foreign marketplaces in the Indonesian online market who have ever made a purchase, have ever felt doubts about doing online transactions with relatively small transaction values. The sampling technique used in this research is a non-probability sampling technique, the sampling method is purposive sampling. The analytical tool used is quantitative to test the hypothesis whether there is an effect of Customer Satisfaction and Interactivity on Repurchase Intentions mediated by Customer Trust and moderated by PEEIM. Research Results. Practical implications of novelty. The research results of the top three foreign marketplaces in the Indonesian online market have been able to build the customer satisfaction, the effectiveness of instant messenger use, the effectiveness of using feedback systems, and the customer trust that affects the customer repurchase intentions. However, it has not been able to create effective interactivity and PEEIM does not moderate both customer satisfaction with customer trust, and customer trust in repurchase intentions and interactivity towards repurchase intentions. This is because the value of online transactions is relatively small so that there is no general perception of respondents in the study. it is about providing protection from potential risks in online transactions. The practical implication of this research is the business strategy that the top three foreign marketplaces in the Indonesian online market have to build in order to form customer repurchase intentions in the same marketplace for relatively small online transactions: PEEIM can be more open, the most important thing that the three big marketplaces from Indonesia have to build it is maintaining customer satisfaction, customer trust and it would be better if it is supported by a high level of communication interactivity. The novelty of this research examines relatively small online transactions in several marketplaces.